6.6k views
1 vote
PLEASE HELP ME!!!!!!!!!!!

PLEASE HELP ME!!!!!!!!!!!-example-1
User Seydhe
by
5.6k points

2 Answers

4 votes

f(-3) = x² - 2x + 3

Plug in -3 for x.

(-3)² - 2(-3) + 3

Distribute the exponent inside the parentheses (-3)^2.

9 - 2(-3) + 3

Multiply -2 * -3.

9 + 6 + 3

Solve from left to right;

18

is your answer.

User Raoul George
by
5.2k points
5 votes


f(x) = x^(2) -2x+3

Since x is equal to -3, substitute all the x's with -3.


(-3)^(2) - 2 \cdot -3 + 3


Parentheses \\ Exponents \\ Multiplication \\ Division \\ Addition \\ Subtraction

Parentheses is first:


(-3)^(2) = -3 * -3 = 9

Next is multiplication:


2 * -3 = -6

The new equation is:


9-(-6)+3

You start from left to right. When you're subtracting a negative number from a positive, the sign changes and you add and the negative number becomes positive.


9-(-6)+3 \rightarrow 9+6+3

Add from left to right:


9+6 = 15

Add 3:


15+3 = 18


f(-3) = \bf 18

User Geoaxis
by
5.0k points